SEJARAH ILMU KALIGRAFI DALAM DUNIA ISLAM - Hafifah Umairah Siregar; Siti Nursina; Wildan Syahputra Hasibuan (Yayasan Haiah Nusratul Islam, 2024)
The history of the science of calligraphy is a description of an event that occurred in ancient times which is then studied with historical data, where this science is categorized as an Islamic art without the interference of non-Muslims, this science can also be said to be a science of someone's imagination through their thoughts. so that beautiful art is formed. One of the things studied in this science is studying the art of Arabic writing which has various writing styles and special writing methods. The existence of this did not just happen, but it underwent a process of development from generation to generation from time to time, starting from the time of the Prophet Muhammad SAW until now. The method used in this study is a descriptive qualitative research method where data collection results are usually obtained from several methods such as interviews, observation, analysis of data obtained from the results of phenomena that occur in the field or data originating from previous research. In this research, the data collection technique uses the library research method by collecting data related to the topic of discussion.